Relación de la salud bucodental de niños con discapacidad auditiva y el conocimiento sobre salud oral de sus padres - Diana Lorena, Castillo Soto (2019)
Hearing impairment is a status characterized by total or partial loss of hearing function, in which there is difficulty in perceiving sound. This condition implies an obstacle for the dentist in communication and care of such patients. The lack of knowledge about oral health in these patients constitutes a trigger for the appearance of oral diseases. The purpose of this research was to relate the oral health of children with hearing impairment and their parents’ oral health knowledge in the “Unidad Educativa Especializada Sordos de Chimborazo” in the city of Riobamba. Surveys were applied to 24 parents of children with hearing impairment. 24 clinical histories of children with hearing impairment were obtained, donated by Promotion and Prevention of the Dentistry career of the National University of Chimborazo, which had the respective informed consent and information on oral health of children. It was concluded that the oral health knowledge of the parents of children with hearing impairment of the “Unidad Educativa Especializada Sordos de Chimborazo” has a significant influence on the oral health status of their children.